1962
DOI: 10.1161/01.cir.26.3.421
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Bilateral Stenosis of the Primary Pulmonary Artery Branches Based on Characteristic Pulmonary Trunk Pressure Curves

Abstract: The cardiac catheterization and angiocardiographic findings in 12 cases with bilateral stenosis of the primary pulmonary artery branches are described. Characteristic pressure tracings were consistently obtained from the main pulmonary trunk in all cases. These typical curves were reproduced in animal experiments. Associated lesions with left-to-right shunts and mild pulmonary valvular stenosis did not alter the characteristics of the curves. An attempt is made to explain these hemodynamic phenomena. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Observations of the pressure pulses proximal and distal to the zones of obstruction show that continuous gradients are not the rule. The central pulmonary artery pulse is characterized by a raised systolic pressure but a rapid fall to a diastolic level that is normal or nearly so (Agustsson et al, 1962) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations of the pressure pulses proximal and distal to the zones of obstruction show that continuous gradients are not the rule. The central pulmonary artery pulse is characterized by a raised systolic pressure but a rapid fall to a diastolic level that is normal or nearly so (Agustsson et al, 1962) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, membranous obstruction occurs just above the pulmonary valve (Franch and Gay, 1963;Arvidsson et al, 1961;Smith, 1958). Pulmonary artery stenosis may be unilateral (Luan et al, 1960) or bilateral (Agustsson et al, 1962), single or multiple (D'Cruz et al, 1964); it may involve a localized arterial site with poststenotic dilatation or varying lengths of a branch from segmental narrowing to diffuse tubular hypoplasia (D'Cruz et al, 1964;Franch and Gay, 1963). Though pulmonary artery stenosis occurs as an isolated congenital malformation, it frequently coexists with other anomalies, especially valvular pulmonary stenosis (Hall et al, 1961;Franch and Gay, 1963;D'Cruz et al, 1964;Rowe, 1963), atrial septal defect (Shafter and Bliss, 1959;Franch and Gay, 1963), ventricular septal defect (D'Cruz et al, 1964), patent ductus arteriosus (Rowe, 1963;D'Cruz et al, 1964;Venables, 1965), and Fallot's tetralogy (Baum et al, 1964;D'Cruz et al, 1964).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason we consider angiography to be essential in differentiating between extrinsic compression and intrinsic obstruction of the pulmonary artery and infundibulum. Agustsson, Arcilla, Gasul, Bicoff, Nassif, and Lendrum (1962), in cases of bilateral pulmonary artery stenosis, described a characteristic waveform in the pressure records taken from the main pulmonary artery, and D'Cruz and his colleagues observed this type of pressure record in most of 52 patients with bilateral pulmonary artery stenosis (D'Cruz, Agustsson, Bicoff, Weinberg, and Arcilla, 1964). We have been unable to find in the literature any example of extrinsic compression of both pulmonary arteries as a cause for this type of pressure tracing and believe that our patient (case 2, Fig.…”
mentioning
confidence: 99%
“…Diagnoses of atrial septal defects (Case 5, ostium primum) were confirmed by cardiac catheterization in six patients (Table II) and at open operation in two (one of whom was catheterized elsewhere). In the five subjects studied in our laboratory, coexisting pulmonary branch stenosis was deliberately sought by, (1) careful continuous withdrawal of the catheter tip from the peripheral branches of both right and left pulmonary arteries into the right ventricle, (2) inspection of the contour of the pressure pulse recorded from the main pulmonary artery (Agustsson et al, 1962), and (3) selective pulmonary angiocardiography (Arvidsson, Karnell, and Moller, 1955). The catheter crossed an atrial septal defect in each of the five patients.…”
mentioning
confidence: 99%